MOCVD growth of Pt films using a novel Pt(IV) compound as a precursor. Issue 7 (26th May 2015) - Dorovskikh, Svetlana I.; Zharkova, Galina I.; Zelenina, Ludmila N.; Asanov, Igor P.; Kal'nii, Danila B.; Kokovkin, Vasily V.; Shubin, Yuri V.; Basova, Tamara V.; Morozova, Natalia B.; Hoffmann, Patrik; Knez, Mato; Vahlas, Constantin; et al.
Abstract The Me3Pt(acac)Py compound, trimethyl(pentane‐2, 4‐dionato)platinum(IV)pyridine, is synthesized and, for the first time, characterized by physico‐chemical methods to determine its chemical composition (elemental analysis, IR‐spectroscopy) and thermal behavior (thermogravimetric (TG), differential thermal analyses (DTA), differential scanning calorimetry (DSC), tensometric flow method). Due to its good volatility ln(p/p°) = 16.47–9699/T(K) at moderate temperatures (393–414 K) the compound is offered as a promising precursor for growth of Pt films by metal‐organic chemical vapour deposition (MOCVD). The Pt films deposited on various substrates including Si(100), Ta, Ti substrates, cathodes and anodes of the electrodes for pacemakers are investigated by X‐ray diffraction (XRD), scanning electron microscopy (SEM) and X‐ray photoelectron spectroscopy (XPS). The electrochemical characteristics of Pt films are also determined. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)